The Natural Park of Montesinho, Bragança, Portugal: territory, ethnobotany and cultural identity - Carvalho, Ana Maria (2017)
The Natural Park of Montesinho is a natural protected area in the Northeastern Portugal created in 1979 in order to preserve the existing environmental qualities and enhance important biocultural patrimony, developed for a long interaction between humans and nature. A territory of 75000 ha that included 91 communities and nearly 8,000 residents in 2011, distributed by two municipalities (Bragança a and Vinhais). It is one of the largest natural parks of the 13 existing ones in Portugal. Two of the most important mountain ranges (Serras) are Serra de Montesinho (north of Bragança a) and Serra da Coroa (north of Vinhais). Elevation varies between 1486 meters in Montesinho and 438 meters in Mente riverbed (Vinhais). Geography, climate and soil conditions along with particular land management carried out over centuries have contributed to an extraordinary diversity of habitats, wildlife and plant communities, a differential biodiversity of great significance at national, Iberian and European levels. There is still a rich socio-cultural patrimony, combining ancestral traditions and some innovation, marked by festivals, religious ceremonies and many reasons for the reunion all over the year of families and neighbours. Some examples are the All Saints’ Day and the pig slaughters, St. Stephen’s Day and the winter solstice feasts. Traditional music and the sounds of bagpipes are other important aspects of the regional identity. Local architecture (e.g. stone roofs, water mills, dovecotes and forges), using the characteristic materials available according to particular knowledge and skills is also remarkable. Montesinho and the neighboring communities of França and Portelo are strongly connected by polychromatic landscape and the paths of shepherds, miners and smugglers. Rio de Onor is also an emblematic village with distinguished significant features: (i) the international border runs across the village dividing it in two sides. Rihonor de Castilla is the Spanish side, and Rio de Onor, the Portuguese one; (ii) a communitarian governance surviving to the end of XX century, based in collective resource management and mutual help among residents, controlled through a community board, where every household involved with the collective property was represented; (iii) an own dialect belonging to the Astur-Leonese linguistic group.